Bioconjugates: A New Class of Therapeutics for Cancer Treatment (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Bioconjugates represent a novel class of therapeutics that offer promise in the treatment of cancer. These compounds are formed by combining a targeting molecule, such as an antibody or peptide, with a therapeutic agent, such as a chemotherapy drug or toxin. This approach allows for targeted delivery of the therapeutic agent to cancer cells, minimizing damage to healthy tissues and reducing side effects. Bioconjugates have shown significant potential in preclinical and clinical studies, with several FDA-approved drugs currently available for the treatment of cancer.There are several types of bioconjugates currently being developed for cancer treatment, including antibody-drug conjugates (ADCs), peptide-drug conjugates (PDCs), and nanoparticle-drug conjugates (NDCs). ADCs are the most well-established type of bioconjugate and have been approved for the treatment of several types of cancer, including breast cancer, lymphoma, and leukemia. PDCs and NDCs are newer classes of bioconjugates that are still in the preclinical and early clinical stages of development. Ongoing research in this field aims to improve the efficacy and safety of bioconjugates and expand their use to a wider range of cancer types. As research in this field continues to advance, we can expect to see even more innovative and effective bioconjugate drugs being developed in the future. These drugs are designed to target specific cancer cells, while leaving healthy cells unharmed, and have the potential to revolutionize cancer treatment. Furthermore, bioconjugates can be tailored to individual patients, allowing for personalized and targeted cancer therapy.